Oxidation resistance and thermal stability of Ti(C, N) and Ti(C, N, O) coatings deposited by chemical vapor deposition. (January 2016) - Zhu, Lihui; Zhang, Yumeng; Hu, Tao; Leicht, Peter; Liu, Yixiong
Abstract: Ti0.51 C0.24 N0.25 and Ti0.51 C0.26 N0.21 O0.02 coatings were deposited by medium temperature chemical vapor deposition, their oxidation resistance and thermal stability at 600 °C were compared. Ti(C, N, O) coating is oxidized faster than Ti(C, N) coating. The oxidation resistance of Ti(C, N, O) coating is impaired not only by the existence of more pores, fissures and cracks in the oxide layer, but also by lower interfacial adhesion. Higher tensile stress has a negative impact on the oxidation resistance of Ti(C, N, O) coating. It promotes the formation and development of more defects and cracks during cyclic oxidation, it is also harmful to the interfacial adhesion. Although the oxidation resistance of Ti(C, N, O) coating is inferior, the thermal stability is improved. The incorporation of oxygen slows down the phase transformation of Ti(C, N, O) at 600 °C. During the annealing, the hardness of Ti(C, N, O) coating is always higher than that of Ti(C, N). Highlights: The oxidation resistance of CVD Ti(C, N, O) coating is inferior. The thermal stability of CVD Ti(C, N, O) coating is improved. The oxidation behavior of Ti(C, N) and Ti(C, N, O) coatings was explained. High tensile stress of CVD Ti(C, N, O) is harmful to the oxidation resistance.